Elobixibat Effectively Relieves Chronic Constipation in Patients with Cancer Regardless of the Amount of Food Intake. (16th July 2021) - Ozaki, Anna; Kessoku, Takaomi; Kasai, Yuki; Takeda, Yuma; Okubo, Naoki; Iwaki, Michihiro; Kobayashi, Takashi; Yoshihara, Tsutomu; Honda, Yasushi; Fuyuki, Akiko; Higurashi, Takuma; Ishiki, Hiroto; et al.
Abstract: Background: Constipation is a common, distressing complication in patients with cancer receiving palliative care. Elobixibat is a novel inhibitor of the ileal bile acid transporter that is used to treat chronic constipation by stimulating bowel function. However, its efficacy in patients with cancer has not been examined. This study investigated the drug's effectiveness in patients with cancer with chronic constipation. Patients and Methods: This prospective-sampling, single-center, observational study included hospitalized patients with cancer diagnosed, using the Rome IV criteria, with chronic constipation. Within 2 weeks of hospitalization, each participant was administered elobixibat (5–15 mg) daily until discharge. Spontaneous bowel movements (SBMs), complete spontaneous bowel movements (CSBMs), Bristol stool form scale (BSFS) scores, and the Patient Assessment of Constipation Quality of Life questionnaire (PAC-QOL) scores were assessed before and after elobixibat administration. We also evaluated the relationship between the amount of food consumed and the SBM frequency. Results: Among the 83 participants, the mean pre- and post-treatment frequencies of daily SBMs were 0.3 and 1.2 ( p < .0001) and those of CSBMs were 0.1 and 0.6 ( p < .0001), respectively. The mean pretreatment BSFS score was 1.6, whereas the post-treatment value was 3.5 ( p < .0001); the mean PAC-QOL score (overall) improved from 1.01 to 0.74 ( p = .01). There was no significant change in the daily SBM frequency between fasting and feeding states (1.2 vs. 1.3; p = .8), and there was no correlation between the amount of food intake and the SBM frequency after elobixibat administration ( r = .03). Serious adverse events were not observed. Conclusion: This study showed that elobixibat is safe and effective for patients with cancer with chronic constipation, regardless of the food intake amount. Implications for Practice: Elobixibat was effective at relieving chronic constipation in patients with various cancers. Serious adverse events were not observed, and the relief of constipation was independent of variation in food intake. Abstract : Constipation is a common, distressing complication in cancer patients receiving palliative care. This study investigated the effectiveness of elobixibat in cancer patients with chronic constipation.